Properties of Ternary Biopolymer Nanocomplexes of Zein, Sodium Caseinate, and Propylene Glycol Alginate and Their Functions of Stabilizing High Internal Phase Pickering Emulsions - Sun, Cuixia (Langmuir : the ACS journal of surfaces and colloids, 2018)
A pH-cycle method based on preparing an alkaline solution of zein followed by neutralization with an acid can be used to prepare zein nanoparticles. In the present work, partial alkaline hydrolysis of propylene glycol alginate (PGA) to a lower pH was studied to prepare binary zein-PGA nanocomplexes and ternary complexes with additional sodium caseinate (NaCas). 0.5% or more PGA was sufficient to reduce the pH to 7.5 or lower, eliminating the need for titration, and resulted in simultaneous nanocomplex formation. The addition of NaCas into alkaline zein-PGA solution resulted in smaller complexes with all biopolymers, whereas adsorption on binary zein-PGA complexes was observed when NaCas was added into the neutral zein-PGA dispersions. The formation of nanocomplexes involved with hydrophobic and electrostatic attractions and hydrogen bonds and was further affected by the amount of NaCas. The ternary nanocomplexes with equal masses of zein and NaCas had an excellent capacity to prepare gel-like Pickering emulsions with as much as 80% v/v oil with characteristics suitable for texture modification and delivery systems of bioactive compounds in food and consumer products. Therefore, PGA can be used to possibly scale-up the pH-cycle method to produce zein-based nanoparticles with unique functional properties